Implementasi Media Konkret Papan Berhitung untuk Meningkatkan Hasil Belajar Matematika di SDN Sukorejo - Bintan Taskurina Hardiningtyas; Bella Mei Gita Lucyana; Muchammad Faiz Agam; Serli Nofita Sari; Shara Habibah (Jurnal Simki Postgraduate, 2024)
This study aims to determine the implementation of concrete media counting boards in improving mathematics learning outcomes at SDN Sukorejo. The study was conducted using the Classroom Action Research method consisting of two cycles. The subjects of the study were 12 grade 1 students. Data was collected through tests, interviews, documentation, and field notes. After the implementation of the counting board media, the results of the study showed a significant increase. The average value in cycle 1 was 51.66 with a completeness of 16.66% (2 students), then increased in cycle 2 to 87.50 with a completeness of 100%. This media has proven to be effective in helping to understand the concept of subtraction through direct experience with concrete objects. This study concludes that the implementation of concrete media counting boards can improve the mathematics learning outcomes of grade 1 students at SDN Sukorejo on the subject of subtraction.